Odpowiedzi

2010-01-09T19:49:32+01:00
1) 2x+ 2= x+6
2) 8(x+2)= 5(x+5)
3) (x+1)²=4x²-3x
4) x²-(x-2)²= 16
5) 4x(x- 2)= (2x +4)²
6) 3(x-1)²- 3x(x-5)=21
7) (x-1)² +(x-2)²= 2(x-1)(x+1)
8) (x+1)²=x²
9)(2x- 3)²= 4x²- 3x
10) x²-(x-2)²=16
11) 4x(x-2)= (2x+4)²
12) 3(x-1)²- 3x(x-5)=21
13) (x+1)²+(x-2)²= 2(x-1)(x+1)
14) (x-3((x+3)/2 - (x+1)²/6= 1/3 x²
15) 3x²-1/3= (x-5)²
16) 3(x +2)²/4 - (x+1)²/6= 1/3 x²
17) 3x+6=-2x+4
18) 3x-1=2x+5
19) x+3/2= x+ 1-3x/6
20) 4- 3x-2/2= 5-1,5x
2010-01-09T19:51:59+01:00
1. 2–(5 + x)=2(3 – x)
2. x + 6 = 2x + 3
3. 2(x + 4) = 8 + 2x
4. (x-1)(x-1) + x-1=2x-2
5. 2(x + 1) = 5
6. 3(x − 3) + 3 = x − 1
7. 2(x − 2) = 14
8. x = 15 − 2x
9. 3(x-3)+3=5x
10. 2t + 4 = 4t − 2
11. 4x – 2 = 1 + x
12. 4*(3x + 2) – 4 = 2*(x - 1) + x
13. 2x – 3 = 8 4x = 5x – 2
14. 6x – 3 = 2x + 5
15. 2(x + 1) = 2x + 2
16. 3x – 5 = 3x + 4 5(x + 1) = 5x – 5
17. x + 6 = 2x + 3
18. 2(x + 1) + x = 3x
19. 4–5(x + 2)=3 – 5x
20. 2(x + 1) + x = 3x